Inferred Weak Rock Mass Classification for Stope Design - Milne, Douglas M. (2013)
Empirical design methods are commonly used for rock mechanics evaluations. An appropriate method of rock mass classification is required to use these empirical methods. There are limitations for rock mass classification methods when access to the ore zone is restricted.